Ustadz Muhammad Eko Marpaung's Social Media Strategy in Spreading Da'wah Content Through Saifullaah's Instagram Social Media Account - Hijri Sarina Putri; Efi Brata Madya (Universitas Muhammadiyah Enrekang, 2024)
Social media is increasingly familiar in Indonesia today and is used in various activities such as entertainment, creativity, business, and so on, including being used as a da'wah medium. Ustadz Muhammad Eko Marpaung is one of the ustadz who uses Instagram as his da'wah medium. This research analyzes the da'wah strategy by Ustadz Muhammad Eko Marpaung through the Instagram account. This research approach is qualitative, with instruments of observation, documentation, and interviews. The subject of this study is Ustadz Muhammad Eko Marpaung as a key informant, then several of his followers who were taken by snowball sampling, and other Instagram users who are seen as able to add information to the needs of this research. Data analysis techniques are done through data reduction, data presentation, and conclusions drawn. Confirmability, credibility, and dependability tests carry out the data validity assurance technique. The study results show that: Ustadz Mhd Eko Marpaung's da'wah strategy through @_Saifullah Instagram account has proven effective in reaching and influencing the audience. This strategy can increase engagement and follower growth by combining educational content, relevance of current issues, and active interaction. In the future, content diversification and feedback management can be areas that need to be considered to increase da'wah's effectiveness further.